2008
DOI: 10.1038/ni1563
|View full text |Cite
|
Sign up to set email alerts
|

The E3 ligase Itch negatively regulates inflammatory signaling pathways by controlling the function of the ubiquitin-editing enzyme A20

Abstract: The ubiquitin-editing enzyme A20 is a critical negative regulator of inflammation and cytokine-mediated activation of the transcription factor NF-kappaB; however, little is known about the mechanisms of A20-mediated inactivation of signaling intermediates such as RIP1. Here we demonstrate that the regulatory molecule TAX1BP1 recruited the E3 ligase Itch to A20 via two 'PPXY' motifs. Itch was essential for the termination of tumor necrosis factor receptor signaling by controlling A20-mediated recruitment and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
287
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 252 publications
(297 citation statements)
references
References 48 publications
10
287
0
Order By: Relevance
“…Interestingly, we found that CYLD, ITCH, TNIP1, TNIP2 and TNIP3, the reported NF-κB-negative regulators [20,29,30], were also the potential targets of miR-486 ( Figure 3B, left panel). Indeed, immunoblotting analysis showed that overexpression of miR-486 repressed, while inhibition of miR-486 increased, the expression levels of CYLD, ITCH, TNIP1, TNIP2 and TNIP3 ( Figure 3B, right panel).…”
Section: Mir-486 Directly Suppresses Multiple Nf-κb Negative Regulatomentioning
confidence: 91%
See 1 more Smart Citation
“…Interestingly, we found that CYLD, ITCH, TNIP1, TNIP2 and TNIP3, the reported NF-κB-negative regulators [20,29,30], were also the potential targets of miR-486 ( Figure 3B, left panel). Indeed, immunoblotting analysis showed that overexpression of miR-486 repressed, while inhibition of miR-486 increased, the expression levels of CYLD, ITCH, TNIP1, TNIP2 and TNIP3 ( Figure 3B, right panel).…”
Section: Mir-486 Directly Suppresses Multiple Nf-κb Negative Regulatomentioning
confidence: 91%
“…How the negative regulatory effect of upregulated A20 on NF-κB signaling is disrupted in gliomas, however, remains unclear. Given that A20 does not have specificity for K63-linked polyubiquitin [29,30,36,37], have been proposed to participate in the NF-κB inhibitory effect of A20 through modulation of A20 activity. For example, ITCH has been found to terminate NF-κB signaling by controlling A20-mediated recruitment and inactivation of RIP1.…”
Section: Discussionmentioning
confidence: 99%
“…Naf1 associates with A20, a zinc finger protein with deubiquitinase activity, and facilitates A20-mediated de-ubiquitination of NEMO/IKK␥ and subsequent NF-B inhibition in response of TNF-␣ (40,54,56). HIV-1-LTR contains the NF-B binding sites, and the suppression of Naf1 on NF-B activation may account for the inhibition of HIV-1 promoter LTR-driven gene expression and viral infection.…”
Section: Discussionmentioning
confidence: 99%
“…81 The RING domain E3 RNF11 was also reported to participate in the ubiquitin-mediated degradation of RIP1 after TNF-a treatment in collaboration with TAXBP1 and Itch. 82 The precise roles for each E3 recruited to the A20 ubiquitin-editing enzyme will be interesting to decipher.…”
Section: Dr Signaling Is Regulated By Ubiquitinationmentioning
confidence: 99%